Effects of Glucose Fluctuations on Electrocardiogram Readings and the Development of Ventricular Arrhythmia in Diabetic Rats - Li-Da Wu; Feng Li; Chao Wang; Shi-Peng Dang; Feng Xiao; Zhen-Ye Zhang; Jie Zhang; Yu-Min Zhang; Cun-Yu Lu; Ying Liu; Guo-Qiang Zhong; Ling-Ling Qian; et al. (Cardiology Discovery)
Objective:. Many studies have shown that blood glucose fluctuations (GFs) are more harmful to patients with diabetes mellitus (DM) than sustained hyperglycemia. However, the effect of GF on electrocardiogram (ECG) parameters and vulnerability to ventricular tachycardia/fibrillation (VT/VF) remains poorly characterized. This study aimed to assess the effect of GF on ECG parameters and induction of VT/VF in streptozotocin (STZ)-induced diabetic Sprague-Dawley rats. Methods:. Male Sprague-Dawley rats were injected with STZ and randomly divided into 3 treatment groups: controlled STZ-induced diabetic rats (C-STZ) (n = 10); uncontrolled STZ-induced diabetic rats (U-STZ) (n = 10); and STZ-induced diabetic rats with glucose fluctuations (GF-STZ) (n = 10). After 12 weeks, baseline ECG recordings were taken and a VT/VF test was performed with the administration of caffeine and dobutamine. Hematoxylin & eosin and masson staining were used to evaluate pathological cardiac changes after intervention. Results:. No significant difference in heart rate, RR interval, P wave (duration and height), PR segment, PR interval, QRS wave duration, and T wave height was observed among the 3 groups (P > 0.05). Compared with the C-STZ group, the U-STZ and GF-STZ groups both had a longer T wave duration ((62.41 ± 2.38) ms vs. (78.37 ± 4.64) ms and (96.06 ± 4.60) ms, P < 0.05), QT interval ((83.66 ± 2.31) ms vs. (101.75 ± 4.56) ms and (119.14 ± 4.88) ms, P < 0.05), and QTc interval ((77.45 ± 1.36) ms vs. (91.36 ± 3.49) ms and (104.55 ± 3.01) ms, P < 0.05), all of which were longest in the GF-STZ group (P < 0.05). Additionally, the GF-STZ group had the highest VT/VF occurrence and duration and the highest arrhythmia score. Conclusion:. This study revealed GF can significantly prolong the QT interval, QTc interval, and T wave duration, as well as increase vulnerability to VT/VF in rats, which may be an important electrophysiological mechanism of GF-related ventricular arrhythmia.